ANALISIS STRUKTUR MODAL PETANI PADI DI KABUPATEN MAGETAN - , RHAMA APRIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to determine (1) the influence of production land factors, seed, fertilizer, pesticides and labor for rice production, (2) the capital structure of rice farmers and (3) find out what factors influence the decision-making external capital. The method used is descriptive analysis. Sampling using simple random sampling method were carried out in Magetan district with a total sample of 30 respondents. The analytical method used is multiple regression analysis and logit methods. The results showed that the factor that significantly affect the production of rice farming is the seed. Seed production is one of the important factors which farmers set aside about 0.95% each harvest to be used on the next farm. In the implementation of farming, the use of equity capital is more than the external capital. Taking of external capital is significantly influenced by the area of land farmers where increased the area of land per unit area will increase the possibility of taking external capital by 7.50 times than that has the landless lower unit.